Kompetensi Kewirausahaan dengan Keberhasilan Usaha Peternak Sapi Perah Pujon, Malang - Pamela Pamela; Rachmat Pambudy; Ratna Winandi (Jurnal Agribisnis Indonesia, 2016)
Pujon, Malang is the largest milk producer in East Java. Nevertheless, the productivity and farm size are at low level. It indicates that entrepreneurial competencies of dairy farmers at poor level. This research presents the results from depth interview with 105 dairy farmers in Malang Regency, East Java. Based on this information, it can be concluded that entrepreneurial competencies of respondents are at low level on strategic skills, and middle level on leadership and technical management skills, Entrepreneurial competencies are generated positively by personal orientation (interest of dairy farmers in group activities, and risk taking behavior, and demographic characteristic (working experience). It has a positive relationship to successful business. Interest of dairy farmers in group activites improvement could up grade the personal orientation, entrepreneurial competencies, and successful business.